TOPONYM OF DEDARI IN BALI: Focusing On The Rajapala Tale And Mythical Waterfalls - Nozawa, Akiko (The Indonesian Journal of Social Studies, 2025)
This article highlights the local toponym “Dedari” (heavenly nymph) in Bali to explore the symbolic function of the imaginary figure in the historical dynamism of the island’s local ecology. The preliminary research presents macroscopic and microscopic observations based on the mapping of geographical distribution and the author’s 2023–2024 fieldwork. The survey first unveiled the fact that most places named Dedari are related to water such as waterfalls, springs, and streams. In particular, the example of a waterfall called Gerojogan Dedari in Pujungan (Tabanan), which is associated with the human-nymph marriage tale Rajapala, suggests three socio-ecological aspects in the holy waterfall of dedari: 1) hierarchizing spatial order as the “head” in the vertical structure of the world (bhuwana), 2) symbolizing territorial acquisition and boundaries, 3) implying the cultural hybridity brought about by the broad network in early Maritime Asia, in contrast to the closed-image mountain areas of Bali. The case study therefore demonstrates the significance of the toponym of Dedari as the key to rediscovering the epistemological landscape between nature and cosmology in the archaic culture of Bali.